2022
DOI: 10.3390/microorganisms10112240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Peel-Associated Epiphytic Bacteria of Anthocyanin-Rich “Sun Black” and Wild-Type Tomatoes under Organic and Conventional Farming

Abstract: Tomatoes are among the most consumed vegetables worldwide and represent a source of health-beneficial substances. Our study represents the first investigating the peel-associated epiphytic bacteria of red and purple (anthocyanin-rich) tomatoes subjected to organic and conventional farming systems. Proteobacteria was the dominant phylum (relative abundances 79–91%) in all experimental conditions. Enterobacteriaceae represented a large fraction (39.3–47.5%) of the communities, with Buttiauxella and Atlantibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Herein, it was shown that conventional and organic plants have comparable bacterial abundance and richness in substrate, rhizosphere, and fruit samples; however, it was revealed that organic plants endured microbiota dysbiosis characterized by an increase in the relative abundance and dominance of some specific bacterial groups. Comparable phenomena have been reported in other studies with tomato, lettuce, and teak plants [ 67 , 96 , 97 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Herein, it was shown that conventional and organic plants have comparable bacterial abundance and richness in substrate, rhizosphere, and fruit samples; however, it was revealed that organic plants endured microbiota dysbiosis characterized by an increase in the relative abundance and dominance of some specific bacterial groups. Comparable phenomena have been reported in other studies with tomato, lettuce, and teak plants [ 67 , 96 , 97 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our data revealed that tomato core microbiota was dominated by phyla Proteobacteria, Actinobacteria, and Firmicutes in the substrate, rhizosphere, and fruit samples; comparable bacterial diversity has been reported in numerous studies with tomato plants cultivated in soil-based and SCSs [20,27,[63][64][65][66][67][68][69][70]. Together, these findings suggest that, regardless of the cultivation system, tomato plants have evolved a close biological interaction with members of Proteobacteria, Actinobacteria, and Firmicutes.…”
Section: Tomato Core Microbiota In Soilless Culture Systemssupporting
confidence: 85%
“…Besides the importance in the overall vegetable crop cultivation, tomatoes also have a central function in the human diet. They are rich in antioxidants [ 4 ] with beneficial properties from anticancer and immune boosting responses to bowel disease amelioration [ 1 ]. Considering the constant intensification of agricultural practices and artificial selection, tomato plants are more susceptible to soil borne diseases due to their genetic homogeneity [ 5 , 6 ], and the adverse effects caused by climate change are adding more threats to the tomato yields [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, their activity in vivo depends on the bioavailability, the structures of compounds, and the composition and metabolic features of the human gut microbiota. In addition to antioxidant capacity, polyphenols have potential healthy properties for humans as anti-inflammatory, antiallergic, antihypertensive, neuropreventive, analgesic, antiviral, and antimicrobial agents [16,18,19]. These compounds are employed as effective antimicrobial agents in healthcare as an alternative to other treatments and in food preservation [20,21].…”
Section: Introductionmentioning
confidence: 99%